The effect of aging on element plant availability and bacterial counts of mixtures of wood ash and sewage sludge - Yudani Pousada-Ferradás; Socorro Seoane-Labandeira; Miguel Blanco; Avelino Núñez-Delgado (Maderas: Ciencia y Tecnología, 2014)
This study investigated the chemical composition of a mixture of 70% wood ashes (a by-product of timber-industry) and 30% sewage sludge (% dry weight), immediately after preparation and after storage (42 days). The mixture had higher Mehlich 3 extractable Ca, Mg and K concentrations than either component alone, and low plant-available heavy metal concentrations, both immediately after mixing and after storage for up to 6 weeks. The results support the view that mixtures of this type may be useful for liming and fertilizing, given their neutralizing capacity and phyto nutrient concentrations. Furthermore, we compared the survival of Escherichia coli in a wood ash and sewage sludge mixture with their survival in mixtures of sewage sludge and two levels of quicklime. The time needed to eliminate most bacteria was 29 days in the ash-sludge combination, while nine days were required for one of the quicklime-sludge mixtures, and counts were minimal for the quicklime-sludge mixture with a pH>12.